Edukasi Inovasi Peningkatan Minat Anak Sekolah Minggu Melalui Animasi Super Book The Lost Sheep di BNKP Jemaat Persiapan Moria Sidikalang Kecamatan Sidikalang, Kabupaten Dairi - Yesikha Sagala; Destimawati Harefa; Endang Junita Sinaga (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The low attendance of congregational children in participating in Sunday school worship activities, childhood is a time where the complexity of abilities in both the fields of knowledge and religion must be emphasized and formed from the start. The aim of this community service activity aims to increase Sunday school interest in worship attendance. Sunday school Sunday school children. This activity will discuss the importance of the role of students in making positive contributions to society through community service for Sunday school children. Through this service, the team hopes to provide new insight into children who are lacking in participating in Sunday school children's services, and can improve children's interest in attending Sunday school Keywords: ,